Online data analysis at the ESRF bioSAXS beamline, BM29. (21st January 2016) - Brennich, Martha Elisabeth; Kieffer, Jérôme; Bonamis, Guillaume; De Maria Antolinos, Alejandro; Hutin, Stephanie; Pernot, Petra; Round, Adam
Abstract : Low‐latency small‐angle X‐ray scattering (SAXS) data reduction for bioSAXS and real‐time feedback to the users is implemented. Abstract : High‐throughput small‐angle X‐ray scattering on proteins in solution (bioSAXS) at synchrotron sources is a commonly used technique in structural biology, which relies on highly automated data acquisition. Data reduction and primary analysis for bioSAXS experiments consist of a well defined series of individual tasks, the automation of which allows a first easy assessment of the quality of collected data and the adjustment of collection strategies if necessary. This article describes both the logic and the technical implementation of the automated processing pipeline for bioSAXS data at the ESRF BM29 beamline using the EDNA framework.